Pentingnya Pelajaran Aqidah Islam dalam Membentuk Kepribadian Siswa - Shelin Patrisia; Shellanda Monica; Tiara Nurhayati (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
Islamic creed education at Madrasah Ibtidaiyah is essential in forming students' personality. Its importance has grown in today's challenging era due to the increasing influence of foreign cultures that conflict with Islamic values. The purpose of this research is to investigate how much Islamic creed instruction influences the character development of MI Darussalam Pagaralam students. " Data was gathered using a descriptive qualitative approach, including documentation, interviews, and observation. Lessons from Islamic creeds have been found to have a substantial impact on kids' character qualities, including discipline, honesty, responsibility, and respect for parents and teachers. They also enhance students' religious awareness by encouraging daily worship practices. Active teachers, supportive families, and religious programs at school serve as key supporting factors, while limited instructional time and negative social media influences are identified as challenges. The study concludes that Islamic creed education greatly contributes to building students' character foundations, highlighting the need for strengthening curricula and developing innovative teaching methods.